Effect of planting date on Fusarium spp. and Diaporthe/Phomopsis complex incidence and its relationship with soya bean seed quality - Meriles, Jose Manuel (2002)
Fifteen soya bean genotypes from maturity groups IV, V and VI were planted on three dates at Manfredi Experimental Station - INTA, Córdoba Province, Argentina. Seeds were harvested at maturity and evaluated for seed infection by Fusarium spp. and Diaporthe/Phomopsis complex, and for physical and chemical parameters. There was a significant negative correlation between planting date (PD) and fungal incidence (P = 0.05). A higher percentage of fungal incidence at earlier PD was consistent with lower seed weight and volume, higher oil content and no change in protein content. The highest values of fungal incidence were associated with increased oleic acid and decreased linoleic and linolenic acid contents. These results suggest that planting late maturity cultivars or delaying the planting of early and mid-season cultivars may reduce seed infection by Fusarium spp. and Diaporthe/Phomopsis complex.